Integrated Intervention Tool : Integration Strategies for Urban Poor Areas and Disadvantaged Communities - World Bank (World Bank, Washington, DC, 2016)
For the 2014-2020 programming period, the Government of Romania (GoR) is considering a new approach presented by the European Commission (EC) - community-led local development (CLLD). Through CLLD, empowered communities have the opportunity to directly shape and own the process of local development, during all stages of EU - funded interventions, from concept design through implementation. If Romania ultimately pursues CLLD, the critical task facing the government is to design an optimal implementation framework for the new approach - this is precisely the focus and scope of the current integrated intervention tool (IIT). The preparation of this IIT entailed a number of steps, including extensive field work to define relevant subtypes of urban marginalized communities and to review past experiences with urban integration in Romania. This summary covers multiple sections, in line with the key chapters of the main IIT report. It first reviews CLLD's main features and best practice principles at the EU level. It focuses on Romania, making some recommendations for where CLLD can apply and what it will require in terms of coordinating different sources of funding. It also covers the main six stages of operationalizing CLLD in Romania, as follows: launch: preparations through capacity building and information campaigns; call for expressions of interest regarding the potential submission of local integration strategies (LISs); mobilization of the community for the establishment of local action groups (LAG) and development of LIS by each LAG; selection of strategies to be financed; implementation of LISs approved for financing, including selection and implementation of individual projects under these strategies; and phase-out activities and evaluation.